The 12-lead electrocardiogram of the elite female footballer as defined by different interpretation criteria across the competitive season. Issue 10 (3rd October 2022) - Morrison, Barbara; Mohammad, Aleah; Oxborough, David; Somauroo, John; Lindsay, Sarah; Drane, Aimee L.; Shave, Rob; George, Keith
ABSTRACT : Pre-participation screening (PPS), using a 12-lead electrocardiogram (ECG), is recommended to identify athletes at risk of sudden cardiac death (SCD). ECG interpretation criteria have been developed to address the concern arising from high false-positives in athletes. There are limited ECG data in elite female footballers. The aims of this study were to (1) compare the ECG outcomes using three published ECG criteria (European Society of Cardiology [ESC], Seattle, International) in elite female footballers and (2) compare ECG data at three different stages of a competitive season. Eighty-one elite female footballers (21 ± 4 yr) completed a medical assessment, anthropometrics, resting blood pressure and a resting 12-lead ECG. Each 12-lead ECG was interpreted in accordance with (1) ESC; (2) Seattle; (3) International Criteria to determine training-related and non-training-related ECG changes. A subset of thirteen (26 ± 4 yr) footballers had repeated resting ECG tests at three time points across the competitive season. Eighty percent of females had training-related ECG patterns. Sinus bradycardia (65%) and early repolarization (42%) were the most common. Using the ESC Criteria 25% (20/81) of the athletes were considered to have an abnormal ECG, compared to 0% using the Seattle and International Criteria, mainly due to alterations in QT length criteria. There were no clinically significant differences in ECG data across a competitive season. The Seattle and International ECG Criteria significantly reduced the number of ECG false-positives in elite female footballers and the time point of PPS within a competitive season is unlikely to alter the PPS outcomes. Abbreviations: AMSSM: American Medical Society for Sports Medicine; ANOVA: Analysis of Variance; BSA: Body Surface Area; ECG: Electrocardiogram; ESC: European Society of Cardiology; FA: Football Association; FIFA: The Fédération Internationale de Football Association (FIFA); F-MARC: FIFA Medical Assessment and Research Centre; LAE: Left atrial enlargement; LVH: Left ventricular hypertrophy; PPS: Pre-participation screening; SCD: Sudden cardiac death